밭토양에서 폐쇄형 자동 챔버법으로 측정한 아산화질소 농도에 대한 측정 불확도 - 주옥정; Ok Jung Ju; 강남구; Namgoo Kang; 임갑준; Gap June Lim (Hanguk hwangyeong nonghak hoeji, 2020)
BACKGROUND: The closed chamber method is the most commonly used for measuring greenhouse gas emissions from upland fields. This method has the advantages of being simple, easily available and economical. However, uncertainty estimation is essential for accurate assessment of greenhouse gas emissions and verification of emission reductions. The nitrous oxide emissions from upland field is very important for the nitrogen budget in the agriculture sectors. Although assessment of uncertainty components affecting nitrous oxide emission from upland field is necessary to take account of dispersion characteristics, research on these uncertainty components is very rare to date. This study aims at elucidation of influencing factors on measurement uncertainty of nitrous oxide concentrations measured by an automated open closed chamber method from upland field. METHODS AND RESULTS: The nitrous oxide sampling system is located in the upland field in Gyeonggi-do Agricultural Research and Extension Services (37°13′22″ N, 127° 02′22″E). The primary measurement uncertainty components influencing nitrous oxide concentrations (influencing factors) investigated in this research are repeatability, reproducibility and calibration in the aspects of nitrous oxide sampling and analytical instrumentation. The magnitudes of the relative standard uncertainty of each influencing factor are quantified and compared. CONCLUSION: Results of this study show what influencing factors are more important in determination of nitrous oxide concentrations measured using the automated open closed chambers located in the monitoring site. Quantifying the measurement uncertainty of the nitrous oxide concentrations in this study would contribute to improving measurement quality of nitrous oxide fluxes.